Prevalence and Hospital Management of Amphotericin B Deoxycholate-Related Toxicities during Treatment of HIV-Associated Cryptococcal Meningitis in South Africa. - Susan Meiring; Melony Fortuin-de Smidt; Ranmini Kularatne; Halima Dawood; Nelesh P Govender; GERMS-SA (Public Library of Science (PLoS), 2016)
BACKGROUND:We aimed to establish the prevalence of amphotericin B deoxycholate (AmBd)-related toxicities among South African patients with cryptococcosis and determine adherence to international recommendations to prevent, monitor and manage AmBd-related toxicities. METHODS:Clinical data were collected from cases of laboratory-confirmed cryptococcosis at 25 hospitals, October 2012 -February 2013. Anemia was defined as hemoglobin (Hb) concentration <10 g/dl, hypokalemia as serum potassium (K) <3.4 mEq/L and nephrotoxicity as an increase in serum creatinine (Cr) to >1.1 times the upper limit of normal. To determine adherence to toxicity prevention recommendations, we documented whether baseline Hb, K and Cr tests were performed, whether pre-emptive hydration and IV potassium chloride (KCl) was administered prior to 80% and 60% of AmBd doses and whether daily oral KCl supplementation was given ≥60% of the time. To determine adherence to monitoring recommendations, we ascertained whether a daily fluid chart was completed, Hb was monitored weekly and K or Cr were monitored bi-weekly. RESULTS:Of 846 patients, clinical data were available for 76% (642/846), 82% (524/642) of whom received AmBd. Sixty-four per cent (n = 333) had documented baseline laboratory tests, 40% (n = 211) were given pre-emptive hydration and 14% (n = 72) and 19% (n = 101) received intravenous and oral KCl. While on AmBd, 88% (n = 452) had fluid monitoring; 27% (n = 142), 45% (n = 235) and 44% (n = 232) had Hb, K and Cr levels monitored. Toxicities developed frequently during treatment: anemia, 16% (86/524); hypokalemia, 43% (226/524) and nephrotoxicity, 32% (169/524). CONCLUSION:AmBd-related toxicities occurred frequently but were potentially preventable with adequate monitoring, supplemental fluid and electrolyte therapies.